The novel approach for electric power system simulation tools validation; Electrical engineering; Vol. 101, iss. 2 - Suvorov A. A. Aleksey Aleksandrovich; Gusev A. S. Alexander Sergeevich; Andreev M. V. Mikhail Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich (2019, 2019)
Title screen